STRATEGI PENGELOLAAN ZAKAT DALAM PENGENTASAN KEMISKINAN - Irsyad Andriyanto (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2011)
In Islam institutionalized poverty eradication with the charity. Therefore, charity should be managed in a productive and professional so that zakat has participation in realizing the ideals of Islam to the life of a prosperous people. One of the management institutions in Indonesia to manage zakat with trustworthy, transparent, and professional is the Rumah Zakat Indonesia (RZI). This study uses socio-economic approach. The analysis serves to simplify data into a form that is easier to read and interpret. The analysis used in this research is descriptive analysis.